KEMAMPUAN DEFFERED TAX DALAM MENJELASKAN INCOME SMOOTHING - Fran Sayekti; Sekar Akrom Faradiza; Indrawati Poespita Dewi (Universitas Trunojoyo Madura, 2011)
The aim of this research is to examine the ability of deffered tax to explain income smoothing in manufacturing company listed in BEI at 2005-2009. Using discretionary accrual may lead to errors in earnings management forecast due to misclasification of total accrual to discretionary and nondiscretionary accrual. Some research used deffered tax to solve this problem and they concluded deffere tax can be used to detect earnings management better than discretionary accrual. The differences of the rule to preparing income statement between commercial accounting and tax regulation make a differences in the number of profit that used to count the tax of profit. This differences motivate manager to used their discretion to choose accounting method that may lead to decrease the profit or to smooth the income. So we predict that deffered tax as a tool to income smoothing. This research used logistic regression to test the hypothesis and found that discretionary accrual give better explanation to earning management than deffered tax.